Examining the psychological and social predictors of burnout among nurses employed by government: a study of nurses at Gweru provincial hospital, Zimbabwe - Sibanda, Salfina (Midlands State University, 2017)
The purpose of this research was to examine the psychological and social predictors of burnout among nurses employed at the public hospital in Gweru, Zimbabwe. The primary aim was to determine the relationship between occupational and demographic stress factors and burnout levels among nurses. Burnout is defined with the human service as a syndrome of emotional exhaustion, depersonalization and reduced personal accomplishment that occurs among individuals who work with people in some capacity. The study population consisted of 126 male and female nurses from Gweru General Hospital. A disproportionate stratified random sampling procedure was used to meet the sample size. Data was gathered through structured questionnaires which were distributed among nurses who participated in this study. The research design guiding this study was quantitative which enabled the researcher to identify the predictors of burnout among nurses. Regression analysis was used to analyze data. The results indicated organizational constraints, death and dying related stress, and age as significant predictors of burnout among nurses at Gweru General Hospital. Workload, nurse intention to leave and working experience were not found to significantly predict burnout among nurses. It is recommended therefore that, future research should focus on the development and evaluation of interventions to ameliorate burnout among Zimbabwean nurses